PENYALAHGUNAAN KEADAAN SEBAGAI PEMBATAS PEMENUHAN ASAS KESEIMBANGAN DALAM PERJANJIAN : Studi Kasus Perjanjian Kerjasama Program Pelatihan Kerja Management Development Program - Alma Achlina Dwi Putri (2021)
In agreeing, to apply conditions the validity for the agreement as stipulated in Article 1320 of the Civil Code, the agreement's principles must also use, one of which is balance. However, in reality, not all agreements apply the principle of balance because there are parties whose bargaining position is higher; there is no balance between the parties in carrying out the agreement. Writing this journal discusses the forms of abuse of circumstances that result in the non-fulfillment of the principle of balance and applying the principle of balance for the parties in the Management Development Program cooperation agreement. In this writing, the author uses the normative juridical method and the approach to applying the Civil Code law and the case approach to the agreement on the Management Development Program training program. The conclusion is in the job training program agreement because of the economic advantage by the company where the agreement only benefits the company and harms participants who do not participate in determining the contents of the agreement. The non-implementation of the agreement's balance can be seen from the agreement's provisions, which are carried out unilaterally. The conclusion of the agreement carried out unilaterally shows that the balance does not apply in the training program cooperation agreement.